THE ARMY OF THE REPUBLIC OF UZBEKISTAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The Armed Forces of the Republic of Uzbekistan represent a vital component of national defense and security in Central Asia. Since gaining independence from the Soviet Union in 1991, Uzbekistan has prioritized the modernization and development of its military capabilities to address evolving regional and global security challenges. This article provides an in-depth examination of the structure, organization, capabilities, and recent advancements within the Uzbek military. Key topics covered include the historical evolution of Uzbekistan's armed forces, their current structure comprising army, air force, air defense, and naval components, as well as specialized units such as Special Forces. Emphasis is placed on recent modernization efforts, including the procurement of advanced military equipment, investment in training and professional development, and strategic partnerships with international allies. Furthermore, the article explores Uzbekistan's defense industry and its role in promoting self-reliance and innovation within the military sector. Regional security dynamics and international engagements are also discussed, highlighting Uzbekistan's commitment to peacekeeping initiatives and collaborative efforts with neighboring countries and international organizations. Overall, this article offers a comprehensive overview of the Army of the Republic of Uzbekistan, showcasing its evolution, capabilities, challenges, and contributions to regional stability and global security in the 21st century.